FLUORESCENT DIAGNOSIS IN THE MONITORING OF SELF-ADMINISTERED HORMONAL THERAPY IN FEMALE PATIENTS WITH ENDOMETRIAL PRECANCER AND CANCER - O. V. Chulkova; E. V. Filonenko; L. G. Serova; I. I. Makarova (IRBIS LLC, 2016)
The results of a fluorescent diagnosis programme in the monitoring of self-administered hormonal therapy using Alasens (3% solution - 10 ml injected into the uterine cavity) have been analyzed in 53 female patients of reproductive age with endometrial precancer or cancer. The time of exposition to Alasens was 2 hours. The fluorescent diagnostic procedure was carried out in this patient cohort at different stages of therapy: oncological and rehabilitative, as well as at one year after discontinuation of hormonal therapy After comparing the fluorescent and morphological examination data, an early relapse or ongoing process was diagnosed in 9 (16,9%) out of 53 patients